The Reform and Evolution of ASEAN Human Rights Regime: A Communicative Action Perspective - Maulana, Zain; Putra, Husni Amriyanto (JAS (Journal of ASEAN Studies), 2024)
ASEAN has experienced significant progress since the initiation of the ASEAN Community Vision and the incorporation of human rights into its foundations. This development has ignited continuous scholarly discussions over the degree to which the ASEAN human rights framework shape regional identity and impacts member states’ behavior towards human rights. These debates often revolve around two key theoretical approaches: the logic of consequences and the logic of appropriateness. These logics pose challenges in fully understanding the complexity of state behavior, as they are often observed operating simultaneously and interchangeably within state actions. The article investigates the ASEAN human rights regime through the communicative action perspective and its logic of arguing. It employs a qualitative instrumental case study approach, focusing on the ASEAN Intergovernmental Commission on Human Rights (AICHR) and the ASEAN Humanitarian Assistance (AHA) Centre to illuminate the region's evolving human rights strategies. It is characterized by both deliberate reforms and informal adaptations, reflecting a complex interplay of traditional principles, and emerging human rights norms. The findings indicate that ASEAN states are open to being convinced and persuaded by ideas related to human rights instead of dismissing them outright. ASEAN's approach to human rights, while progressing gradually, suggests a shift towards more substantive engagement with global human rights norms, facilitated by the discursive processes embedded within the AICHR and AHA Centre.